Analisis Pendahuluan Pengembangan Media Pembelajaran Matematika Berbasis Android Pada Materi SPLDV: Penelitian - Doli Oktamira; Hafizah Delyana; Melisa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to conduct a preliminary analysis for the development of Android-based mathematics learning media on the topic of Systems of Linear Equations in Two Variables (SPLDV) for eighth-grade students at SMP Negeri 5 Lembah Gumanti. The background of this research is the difficulty students face in understanding SPLDV concepts when relying solely on conventional teaching methods, as well as the limited learning media used by teachers. This study employed a qualitative descriptive approach with data collection techniques including observation, interviews, and questionnaires involving mathematics teachers and eighth-grade students. The results showed that students encountered difficulties in solving SPLDV problems, particularly in problem modeling and the application of elimination and substitution methods. Furthermore, students were more interested in interactive digital media compared to printed books, and teachers also considered that Android-based media has the potential to enhance students’ motivation and comprehension. The analysis of student characteristics indicated that the majority were already familiar with Android devices, making this technology-based learning media suitable for implementation. Findings from interviews and literature reviews also support the need for Android-based learning media with interactive features, adaptive practice questions, and visual simulations.